124k views
0 votes
Drag the tiles to the correct boxes to complete the pair.

Match the pairs of values of f(x) and g(x) with the corresponding values of h(x) if h(x)= f(x)/g(x).

f(x) = x2 - 9, and g(x) = x - 3

f(x) = x2 - 4x + 3, and g(x)= x - 3

f(x) = x2 + 4x - 5, and g(x) = x - 1

f(x) = x2 - 16, and g(x) = x - 4

1.h(x) = x + 5—>
2.h(x) = x + 3—>
3.h(x) = x+4—>
4.h(x) = x-1—>

1 Answer

4 votes

Answer:

1. h(x) = x + 5—> f(x) = x² + 4x - 5, and g(x) = x - 1

2. h(x) = x + 3 —> f(x) = x² - 9, and g(x) = x - 3

3. h(x) = x + 4—> f(x) = x² - 16, and g(x) = x - 4

4.h(x) = x - 1—> f(x) = x² - 4x + 3, and g(x)= x - 3

Explanation:

A) f(x) = x² - 9, and g(x) = x - 3

We are told that; h(x) = f(x)/g(x)

f(x) = x² - 9 can be factorized to;

f(x) = (x + 3)(x - 3)

Thus; h(x) = (x + 3)(x - 3)/(x - 3)

(x - 3) will cancel out to give;

h(x) = x + 3

B) f(x) = x² - 4x + 3, and g(x)= x - 3

x² - 4x + 3 can be factorized as;

(x - 1)(x - 3)

Thus; f(x) = (x - 1)(x - 3)

h(x) = (x - 1)(x - 3)/(x - 3)

h(x) = x - 1

C) f(x) = x² + 4x - 5, and g(x) = x - 1

x² + 4x - 5 can be factorized as;

(x - 1)(x + 5)

Thus; f(x) = (x - 1)(x + 5)

h(x) = (x - 1)(x + 5)/(x - 1)

h(x) = x + 5

D) f(x) = x² - 16, and g(x) = x - 4

x² - 16 can be expressed as;

(x + 4)(x - 4)

Thus; f(x) = (x + 4)(x - 4)

h(x) = (x + 4)(x - 4)/(x - 4)

h(x) = x + 4

User Mantas Astra
by
5.2k points